2012
DOI: 10.1080/00224545.2012.691572
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Biases of the Intermediate-Status Group: The Effect of Stability and Instability of Social Stratification

Abstract: In two studies, the effect of instability of social stratification on intergroup behaviour of the intermediate-status group was investigated. In both studies, participants were categorised in the intermediate-status group. In Study 1, perceived instability was measured. Results show that the more social stratification was perceived as stable, the more intermediate-status group members were biased against the high-status group. Biases against both high- and low-status groups tended to become similar as social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In contrast, when resources were unlimited (a condition which generated more security), intermediate‐status group members were more biased against the high‐status group. In another study, Caricati and Monacelli (, Study 1) experimentally induced psychology students to believe that their university was of intermediate status. They then measured the perceived stability of status differences and intergroup bias in a resources allocation task.…”
Section: Moving Beyond High‐ Versus Low‐status Hierarchy: Triadic Socmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when resources were unlimited (a condition which generated more security), intermediate‐status group members were more biased against the high‐status group. In another study, Caricati and Monacelli (, Study 1) experimentally induced psychology students to believe that their university was of intermediate status. They then measured the perceived stability of status differences and intergroup bias in a resources allocation task.…”
Section: Moving Beyond High‐ Versus Low‐status Hierarchy: Triadic Socmentioning
confidence: 99%
“…Results indicated that the more social stratification was perceived as stable, the more intermediate‐status group members were biased against the high‐status group. In Study 2, Caricati and Monacelli () manipulated the instability of social stratification in status‐ameliorative unstable and status‐detrimental unstable conditions. Results indicated that when instability led intermediate‐status group members to believe that their social position would worsen (i.e., status‐detrimental instability), they were more biased against the low‐status groups.…”
Section: Moving Beyond High‐ Versus Low‐status Hierarchy: Triadic Socmentioning
confidence: 99%
“…They may not obtain positive social comparison and thus they have nothing to achieve by supporting the existing social hierarchy. Intermediate‐status group is still disadvantaged relative to the high‐status group but members can compare the ingroup positively with the low‐status group (Caricati, ; Caricati & Monacelli, ). Thus, intermediate‐status group members, by supporting the existing hierarchy, can maintain the possibility of positively comparing their group with the low‐status groups (Caricati, ).…”
Section: Studymentioning
confidence: 99%
“…Although the latter evidence should be taken cautiously given that mediation analysis had an explorative purpose, on the whole, these results seem to indicate that alliance orientation among intermediate-status groups might be motivated by the desire to maintain (or not worsen) their intermediary social position (at least when social stratification is downwardly unstable), which allows them to achieve positive intergroup comparison via downward comparison. Through alliance with a low-status group, intermediate-status group members can hope to preserve their social position and, more specifically, the possibility of achieving a positive downward comparison [ 7 , 8 , 19 ]. In other words, when social stratification is stable, and other things being equal, alliance with a low-status group loses relevance for intermediate-status group members, given that the positive downward comparison is already ensured.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, one of the hypotheses of TSST is that the intermediate-status group would be primarily concerned with preventing falling than with trying to increase its social position by challenging superior groups [ 2 , 5 – 8 ]. Accordingly, it has been shown that intermediate-status group members are more biased against both high-status and low-status outgroups when social stratification in depicted as unstable rather than stable [e.g., 7 ].…”
Section: Introductionmentioning
confidence: 99%